Mapalus Tradition: North Sulawesi Muslim Society in the Maqashid Syariah Discourse - Yusuf, Nasruddin; Usup, Djamila; Tumiwa, Anisa Jihan; Bilalu, Naskur; Isima, Nurlaila (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2025)
This research explores the alignment and divergence of the principles of Mapalus with Islamic legal and ethical frameworks, contributing to the broader discourse on integrating local wisdom with Islamic values in multicultural societies. Mapalus, a communal tradition rooted in the Christian-majority Minahasan society, has been adopted by the Muslim minority by applying Maqāṣid Syarī’ah principles, particularly in community well-being, justice, and property protection. Through empirical data from interviews with religious leaders and community members, the study highlights how Islamic jurisprudence guides modifications to traditional Mapalus practices, ensuring compliance with religious obligations while preserving core cultural values. The research reveals that while Islamic values of justice, reciprocity, and mutual assistance align with Mapalus' cooperative ethos, certain rituals require adaptation or exclusion to adhere to Islamic law. This integration is facilitated by the involvement of religious leaders, who mediate potential conflicts and help maintain social harmony. The study concludes that Mapalus is a model for successfully integrating local wisdom with Islamic values in a multicultural context, demonstrating the flexibility of cultural practices and religious principles in fostering unity and cooperation across diverse communities.